Efficacy of a Hypotonic Treatment for Peritoneal Dissemination from Gastric Cancer Cells: An In Vivo Evaluation. (1st July 2014) - Shiozaki, Atsushi; Ichikawa, Daisuke; Takemoto, Kenichi; Nako, Yoshito; Nakashima, Shingo; Shimizu, Hiroki; Kitagawa, Maki; Kosuga, Toshiyuki; Konishi, Hirotaka; Komatsu, Shuhei; Fujiwara, Hitoshi; Okamoto, Kazuma; et al.
Abstract : The aim of the present study was to determine the efficacy of a hypotonic treatment for peritoneal dissemination from gastric cancer cells using an in vivo model. We firstly evaluated the toxicity of a peritoneal injection of distilled water (DW) (2 mL for 3 days) in mice. Macroscopic and microscopic examinations revealed that the peritoneal injection of DW did not severely damage the abdominal organs of these mice. MKN45 gastric cancer cells preincubated with NaCl buffer or DW for 20 minutes in vitro were then intraperitoneally injected into nude mice, and the development of dissemination nodules was analyzed. The total number, weight, and volume of the dissemination nodules were significantly decreased by the DW preincubation. We then determined whether the peritoneal injection of DW inhibited the establishment of peritoneal dissemination. After a peritoneal injection of MKN45 cells into nude mice, NaCl buffer or DW was injected into the abdominal cavity for 3 days. The total volume of dissemination nodules was significantly lower in DW-injected mice than in NaCl-injected mice. In conclusion, we demonstrated the safeness of a peritoneal injection of DW. Furthermore, the development of dissemination nodules from gastric cancer cells was prevented by a preincubation with or peritoneal injection of DW.